PENGARUH VARIASI CAMPURAN OLI BEKAS DAN BIOSOLAR TERHADAP KARAKTERSITIK UJI PEMBAKARAN DROPLET - Akhmad Syarief; Ahmad Ramadan; Misbachudin Misbachudin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
This study aims to determine the effect of mixed used oil and biodiesel mixture on droplet combustion test characteristics. . This research was conducted by dripping the fuel at the tip of the thermocouple to form a droplet with a volume of 0.1 mm, then bringing the heater to the droplet to form a fire. This study aims to determine the influence of mixed oil and biosolar of flash point value, ignition delay time, burning rate and maximum fire height. This research used variation of used oil mixture 10%, 20%, 30%, 40% and 50%. The results show that flash point value increases with increasing percentage of used oil, which is influenced by the viscosity, density, and volatility of each variation of fuel mixture. The value of the ignition delay time increases with increasing percentage of used oil, which is influenced by the viscosity, density and volatility of each variation of fuel mixture. The burning rate value decreases with the increase of the used oil mixture, which is influenced by the viscosity, density, and volatility of each variation of fuel mixture. The maximum value of fire that can be achieved decreases, along with the increase of variation of used oil mixture and is influenced by viscosity, density and volatility value and each variation of fuel mixture.